Collagen-producing lung cell atlas identifies multiple subsets with distinct localization and relevance to fibrosis - Tatsuya Tsukui (Nature Portfolio, 2020)
Collagen production by lung cells is critical to maintain organ architecture but can also drive pathological scarring. Here the authors perform single cell RNA sequencing of collagen-producing lung cells identifying a subset of pathologic fibroblasts characterized by Cthrc1 expression which are concentrated within fibroblastic foci in fibrotic lungs and show a pro-fibrotic phenotype.